GLOBAL RESEARCH TREND ON KNOWLEDGE AND ATTITUDE TOWARDS INFERTILITY - Jelemie, Caroline Satu; Baddiri, Baidi; Abd Kassim, Sharinah; Majin, Rosnah; Sa’at, Siti Fatimah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Infertility is increasingly recognized as a global public health concern, not only for its biomedical implications but also for its psychological, social, and cultural dimensions. Understanding the knowledge and attitudes towards infertility is crucial for informing policies, reducing stigma, and enhancing patient-centered care. Despite its importance, research in this area has been scattered, necessitating a comprehensive bibliometric analysis to map trends, collaborations, and thematic developments. The present study addresses this gap by systematically examining global research output on knowledge and attitudes towards infertility. Data were collected using the Scopus database through an advanced search strategy with the keywords “knowledge,” “attitude,” and “infertility,” yielding a total of 1,035 articles. The data were then refined and harmonized using OpenRefine to ensure consistency and accuracy. Statistical and graphical analyses were conducted using the Scopus analyzer, while VOSviewer software was employed to generate network visualizations of co-authorship, co-citation, and keyword co-occurrence patterns. The findings revealed a steady increase in publication output over the past five decades, with a sharp rise after 2010, indicating growing academic attention to the subject. The United States, the United Kingdom, and Australia emerged as the leading contributors, while collaborative networks highlighted increasing involvement from developing countries such as India, Nigeria, and Iran. Keyword co-occurrence analysis identified seven major clusters, reflecting thematic emphases on assisted reproductive technologies, patient awareness, fertility preservation, psychosocial dimensions, and cultural perceptions. These results contribute to the body of knowledge by mapping the intellectual structure and global research dynamics of infertility studies. In conclusion, the study underscores the multidimensional nature of infertility research and highlights the need for strengthened interdisciplinary and international collaborations to address this complex health issue.